Assessment of the Potential for Greenhouse Gas Emission Mitigation by the Methanization of Slaughterhouse Waste in the District of Abidjan (Côte d'Ivoire) - Tiangoua Kone; Amenan Lydie Clarisse Mangoua-Allali; Assamoi Béatrice Ama-Cauphys; Pantchie Hadidjata Kone; Pétémanagnan Jean-Marie Ouattara; Lacina Coulibaly (European Scientific Journal, ESJ, 2022)
Abattoirs are source of huge amounts of waste that contribute to global greenhouse gas (GHG) emissions and thus, to the global warming and climate change. Treating these was with biodigester technology could be a suitable alternative to GHG emission mitigation. The objective of this study is to evaluate the potential for GHG emission mitigation by a biodigester to be installed at the abattoir of Port-Bouët in the District of Abidjan as a pilot project. More specifically, it aims to: (i) estimate the daily biogas production from 2013 to 2018 according to the mathematical methods of Hashimoto, Gwogon, and Amahrouch, and an empirical method, (ii) evaluate the environmental benefits of the biodigester by estimating the avoided GHG emissions according to the methods mentioned above.The mathematical methods used are those of Hashimoto, Gwogon and Amahrouch. In addition, the empirical method was also used. The results showed that regardless of the method, the amount of biogas increased from 2013 to 2017 and decreased in 2018. The highest daily biogas productions are obtained in 2017 for all methods. Thus, the biogas volumes are 564.50 m3 in a biodigester of 2792.64 m3 according to the Hashimoto method, 724.15 m3 for the biodigester of 2228.14 m3 with the Gwogon method and 557.03 m3 for digesters of volumes 2785.17 m3 calculated with the Amahrouch method. According to the empirical method, the maximum volume of biogas is 631.31 m3. Regarding the amount of CO2 avoided per kilogram of dung, the values ranged from 41579.88 to 71561.17 kg CO2e for the Gwogon method, 41643.46 to 71670.58 kg CO2e for the empirical method, 41689.19 to 71749.30 kg CO2e for the Hashimoto method, and 41694.30 to 71758.10 kg CO2e for the Amahrouch method. These results show a great environmental and economic potential of the installation of a biodigester for the treatment of the waste of the slaughterhouse of Port-Bouët. The choice of the anaerobic digestion process was a continuous mixed biodigester where the substrate is introduced daily with liquid.